Сильная суммируемость ортогональных разложений суммируемых функций. I - Степанец, А.И.; Ласурия, Р.А. (Український математичний журнал, 1996)
We study the problem of strong summability of Fourier series in orthonormal systems of polynomial-type functions and establish local characteristics of the points of strong summability of series of this sort for summable functions. It is shown that the set of these points is a set of full measure in the region of uniform boundedness of systems under consideration.